1992
DOI: 10.1017/s0025100300004588
|View full text |Cite
|
Sign up to set email alerts
|

Turkish

Abstract: The speech is that of a 25 year old native of Istanbul. This variety of the language is considered standard; most educated speakers of Turkish are familiar with this pronunciation as well as a regional variety. Consonants Plosive and Affricate Nasal Fricative Tap Approximant Lateral Approx. Bilabial 'wire' 'pierce' 'horseshoe' 'vote' 'rap' 'membrane' 'pine' 'glass' 'servant' 'tulip' c car 'profit' j jem 'bit (for a horse)' k kar 'snow' g gam 'grief Y day [da:] 'mountain' h her 'every' j jer 'place'

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…Sonuç olarak, Türkçe sesletim çalışmalarında kullanılan örnek metin Rüzgâr ile Güneş (Zimmer ve Orgun, 1992) olmuştur. İngilizce alan yazında son yıllarda 'The Boy Who Cried Wolf'-Yalancı Çoban (Deterding, 2006) yaygın olarak kullanılmaya başlanmıştır.…”
Section: Türkçe Sesletim çAlışmalarında Kullanılan Materyallere Genel...unclassified
See 1 more Smart Citation
“…Sonuç olarak, Türkçe sesletim çalışmalarında kullanılan örnek metin Rüzgâr ile Güneş (Zimmer ve Orgun, 1992) olmuştur. İngilizce alan yazında son yıllarda 'The Boy Who Cried Wolf'-Yalancı Çoban (Deterding, 2006) yaygın olarak kullanılmaya başlanmıştır.…”
Section: Türkçe Sesletim çAlışmalarında Kullanılan Materyallere Genel...unclassified
“…Türkçe'nin sesbilgisi tanımının yapıldığı çalışmalara baktığımızda da bu metinlerin Türkçeleştirilmiş versiyonunun kullanıldığına rastlamaktayız (Bkz, Zimmer ve Orgun, 1992). Zimmer ve Orgun (1992) Rüzgâr ile Güneş metnini kullanarak Türkçedeki seslerin sesbirim betimlemelerini yapmıştır. Deterding (2006) çalışmasında bu metnin İngilizcenin sesbilgisi açısından yeterli örnekleri içermediğini tartışarak alternatif bir metin önermiş ve bu metin (Yalancı Çoban) son yıllarda yapılan İngilizce sesbilgisi çalışmalarında yaygın olarak kullanılmıştır.…”
Section: Introductionunclassified
“…We provide phonemic, phonetic, and orthographic transcriptions of 'The North Wind and the Sun' in the Cwyzhy dialect, translated from the Turkish version (Zimmer & Orgun 1992) by Mr. Pysipa. 'The North Wind and the Sun' has also been translated into the literary Abzhywa dialect by Zaira Khiba (published by Hewitt 1978).…”
Section: Transcription Of Recorded Passagementioning
confidence: 99%
“…According to Altmann (2006), Turkish speakers have difficulty with English stress timing and unstress. Word stress is usually on the final syllable but may be moved to penultimate for morphological reasons (Zimmer & Orgun, 1992) so irregular English stress may be a problem. Demirezen (2016) also found that coarticulation is a serious problem for Turkish learners.…”
Section: Turkishmentioning
confidence: 99%